Embryo selection in IVF - Sebastiaan Mastenbroek; Fulco van der Veen; Abbas Aflatoonian; B. Shapiro; Patrick M. Bossuyt; Sjoerd Repping (2011)
To optimize success rates of IVF, selection of the most viable embryo(s) for transfer has always been essential, as embryos that are cryopreserved are thought to have a reduced chance of implanting after thawing. Recent developments challenge this concept. Evidence is accumulating that all embryos can now be cryopreserved and transferred in subsequent cycles without impairing pregnancy rates or maybe even with an improvement in pregnancy rates. In such a scenario no selection method will ever lead to improved live birth rates, as, by definition, the live birth rate per stimulated IVF cycle can never be improved when all embryos are serially transferred. In fact, selection could then only lower the live birth rate after IVF. The only parameter that could possibly be improved by embryo selection would be time to pregnancy, if embryos with the highest implantation potential are transferred first.